2014
DOI: 10.1111/lam.12361
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between structure and in vitro antibacterial activity of selected isoflavones and their metabolites with special focus on antistaphylococcal effect of demethyltexasin

Abstract: The results of the structure-activity relationship (SAR) analysis identified ortho-dihydroxyisoflavones as a class of antibacterially effective compounds emphasizing the hydroxyl groups at C-5, 6 and 7 positions as crucial supposition for the antibacterial action of plant isoflavones and their metabolites. Demethyltexasin, an isoflavones' metabolite present in the human body through enterohepatic recycling of soya bean isoflavones (daidzein, genistein), showed the most potent antibacterial activity, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 27 publications
(59 reference statements)
2
25
0
Order By: Relevance
“…The results reported by Hummelova et al . 25 agree partially with our observations, since the isoflavonoids with the strongest S . aureus inhibitory effect were ortho -dihydroxyisoflavones.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results reported by Hummelova et al . 25 agree partially with our observations, since the isoflavonoids with the strongest S . aureus inhibitory effect were ortho -dihydroxyisoflavones.…”
Section: Discussionsupporting
confidence: 92%
“…aureus inhibitory effect were ortho -dihydroxyisoflavones. Other studies showed that 5,7-dihydroxylation of the flavonoid A-ring was important for anti-MRSA activity 25, 50, 51 and monomethoxy B-ring derivatives were generally found to be more active (antibiotic synergy) than the disubstituted B-ring derivatives 29 .…”
Section: Discussionmentioning
confidence: 97%
“…This observation is in correspondence with previously published reports describing orthodihydroxy groups as the most important structural feature of high biological activity for phenolic compounds (e.g., stilbenes scavenging radicals) [29]. In addition, the increasing effect of antibacterial activity due to the presence of orthodihydroxy groups in structure of selected various classes of polyphenols, such as isoflavones, has also previously been proposed [31].…”
Section: Discussionsupporting
confidence: 90%
“…A n t i m i c r o b i a l s t u d i e s o f i s o l a t e d isoflavone are rarely found in literature. The isoflavone 6,7,4'-trihydroxy-isoflavone showed antibacterial activity against Bacillus cereus ATCC 11778, Listeria monocytogenes ATCC 7644, Staphylococcus aureus ATCC 29213, Staphylococcus epidermidis ATCC 12228 and Streptococcus pyogenes ATCC 19615 at concentrations of 32, 128, 16, 32 and 64 μg/ml (Hummelova et al 2014).…”
Section: Oxidation Inhibition With β-Carotene and Linoleic Acid (Bcb)mentioning
confidence: 99%